Job Characteristics, Workload, and Their Impacts on the Job Satisfaction of Expatriate Academics - Almohammad, Dawoud; Kilic, Cumali; Bek, Danya Raouf; Ammari, Mohammad Tarek; Hasan, Huda; Sandeh, Mustafa (Journal of Ecohumanism, 2024)
This research investigates how workload and job characteristics impact job satisfaction among expatriate academics at Turkish universities. Using a quantitative approach, a questionnaire in Turkish, English, and Arabic was distributed by expatriate academics across various Turkish universities. A total of 132 responses were analyzed. Results indicate that attitudes toward workload are generally neutral, likely due to varying workloads by position and location, which affects job satisfaction. Job autonomy and job clarity significantly improve job satisfaction by offering flexibility and clear expectations, respectively. In contrast, a higher workload correlates with reduced satisfaction, as it increases stress and diminishes recognition, ultimately impacting performance. The study may lack generalizability due to the limited range of nationalities and majors among participants and its focus on expatriate academics. Future research could explore other expatriate types in diverse cultural settings. To enhance job satisfaction, institutions should balance workloads, boost job autonomy, and provide clear roles while fostering a supportive environment. These measures may mitigate overload and support expatriates’ job satisfaction and productivity. This study uniquely addresses expatriate academics' challenges, offering valuable insights into supporting their well-being and performance.